Rescue stem cell mobilization with plerixafor economizes leukapheresis in patients with multiple myeloma - Hundemer, Michael; Engelhardt, Melanie; Bruckner, Thomas; Schmitt, Anita; Sauer, Sandra; Neben, Kai; Witzens-Harig, Mathias; Goldschmidt, Hartmut; Ho, Anthony Dick; Wuchter, Patrick (Journal of clinical apheresis, 2014)
While extensive data demonstrated that plerixafor improves stem cell harvest in difficult-to-mobilize patients, economic concerns limit a broader application. We retrospectively assessed the effect of an early plerixafor rescue regimen for mobilization in patients with multiple myeloma. Patients were intended for high-dose chemotherapy followed by autologous peripheral blood stem cell transplantation (ABSCT) and therefore received cyclophosphamide-based mobilization chemotherapy and consecutive stimulation with granulocyte colony-stimulating factor (G-CSF). Fifteen patients with poor stem cell harvest in the first leukapheresis session received plerixafor. Data were compared with a matched historic control group of 45 patients who also had a poor stem cell yield in the first apheresis session, but continued mobilization with G-CSF alone. Patients in the plerixafor group collected significantly more CD34+ cells in total (median 4.9 vs. 3.7 [range 1.6-14.1 vs. 1.1-8.0] × 106 CD34+ cells /kg bw; P < 0.05), and also more CD34+ cells per leukapheresis procedure (P < 0.001). Consequently, they required a significantly lower number of leukapheresis procedures to achieve the collection goal (median 2.0 vs. 4.0 [range 2-3 vs. 2-9] procedures; P < 0.001). The efficiency of the collected stem cells in terms of hematologic engraftment after ABSCT was found to be equal in both groups. These data demonstrate that rescue mobilization with plerixafor triggered by a low stem cell yield in the first leukapheresis session is effective. Although the actual economic benefit may vary depending on the local leukapheresis costs, the median saving of two leukapheresis procedures offsets most of the expenses for the substance in this setting. An exemplary cost calculation is provided to illustrate this effect.